Periodontal disease in patients with chronic coronary heart disease: Prevalence and association with cardiovascular risk factors - Ola Vedin (2018)
© 2014 The European Society of Cardiology. Aim: There are reported links between periodontal disease (PD) and cardiovascular (CV) risk but data are lacking, especially from populations with established coronary heart disease (CHD). This study describes self-reported indicators of PD and associations with CV risk factors in a global stable CHD population. Methods and results: A total of 15,828 participants in the global STABILITY trial underwent a physical examination, blood sampling, and completed a lifestyle questionnaire. They reported remaining number of teeth (none, 1-14, 15-20, 21-25 or 26-32 (all)) and frequency of gum bleeding (never/rarely, sometimes, often or always). Adjusted linear and logistic regression models assessed associations between tooth loss, gum bleeding, and socioeconomic and CV risk factors. A total of 40.9% of participants had <15 remaining teeth; 16.4% had no teeth; and 25.6% reported gum bleeding with large differences in prevalence among countries, regions and ethnic groups. Less tooth loss was associated with lower levels of glucose, low-density lipoprotein (LDL) cholesterol, systolic blood pressure, waist circumference and hs-CRP; higher estimated glomerular filtration rate; decreased odds for diabetes and smoking, and increased odds for higher education, alcohol consumption and work stress. Gum bleeding was associated with higher LDL cholesterol and systolic blood pressure; decreased odds for smoking, but increased odds for higher education, alcohol consumption and stress. Conclusion: Self-reported indicators of PD were common in this chronic CHD population and were associated with an increasing socioeconomic and CV risk factor burden. However, causality between self-reported PD and CV risk and outcome needs further investigation.